Estoque de carbono e atributos físicos de um Latossolo em cronossequência sob diferentes manejos - Rossetti, Karina de V. [UNESP]; Centurion, Jose F. [UNESP] (Univ Federal Campina Grande, 2015)
The aim of this study was to determine the effect of the no-tillage planting systems (NT) under different years of implantation and of conventional tillage, growing soybeans and maize for two crop years, on carbon stocks and physical attributes of a Red Oxisol in comparison to native forest. A completely randomized design with split-plots (five treatments and three layers) was used, with four replications. The treatments in 2008/ 09 were: NT with 5 (NT5); NT with 7 (NT7); NT with 9 (NT9) years of implantation, conventional tillage (CT) and a native forest area (NF). The treatments extended to the year 2009/10, identified as: NT6, NT8, NT10 and CT and NF; the studied soil layers were: 0-10, 10-20 and 20-30 cm. The results obtained showed that most of the treatments maintained the carbon stock content (CS) during transition from the surface layer to the underground layer. CS was more pronounced in the surface layer and, within it, the NT9 and NT10 were the most relevant in comparison to the other conservationist systems.

Propôs, neste trabalho, determinar o efeito do sistema plantio direto (SPD) sob diferentes anos de implantação e do preparo convencional (SPC) cultivados por dois anos agrícolas, com soja e milho, sobre os estoques de carbono e atributos físicos de um Latossolo Vermelho em comparação com a mata nativa. O delineamento foi inteiramente casualizado, em parcelas subdivididas (cinco tratamentos e três camadas), com quatro repetições. Os tratamentos em 2008/09 foram: SPD com 5 (SPD5), SPD com 7 (SPD7), SPD com 9 (SPD9) anos de implantação, SPC e uma área de mata nativa (MN). Os tratamentos se estenderam para o ano de 2009/10, assim identificados: SPD6, SPD8, SPD10 e SPC e MN; as camadas de solo estudadas foram: 0-10, 10-20 e 20-30 cm. Os resultados obtidos mostraram que a maioria dos tratamentos manteve o teor do estoque de carbono (EC) durante a transição da camada superficial para a subsuperficial. O maior EC foi mais pronunciado na camada superficial na qual os SPD9 e SPD10 foram os mais relevantes em comparação com os demais sistemas conservacionistas.
Carbon stock and physical attributes of an Oxisol in chronosequence under different managements practices
Keywords: Soil organic matter; No-tillage; Conventional tillage